2017
DOI: 10.3386/w23252
|View full text |Cite
|
Sign up to set email alerts
|

How Debit Cards Enable the Poor to Save More

Abstract: We study an at-scale natural experiment in which debit cards are given to cash transfer recipients who already have a bank account. Using administrative account data and household surveys, we find that beneficiaries accumulate a savings stock equal to 2 percent of annual income after two years with the card. The increase in formal savings represents an increase in overall savings, financed by a reduction in current consumption. There are two mechanisms: first, debit cards reduce transaction costs of accessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 37 publications
2
52
1
1
Order By: Relevance
“…Likewise, storing cash at home is difficult "because such sums are easily eroded by many kinds of risk and pressure: they can be stolen or lost, or used up in trivial expenditure, or claimed by family and neighbours falling on hard times" (Rutherford, 2000, p. 11-12). Bachas et al (2016) provide evidence from Mexico that saving informally is difficult and using bank accounts to save helps solve self-control problems. As reported by Rutherford (2003) and Nasrin et al (2016), most slum dwellers in Dhaka do not hold bank accounts; and those who do rarely use them because "bank norms are so stiff that it is not convenient to use [them] regularly" (Rutherford, 2003, p. 51 (Ashraf et al, 2006;de Mel et al, 2013).…”
Section: Datasetmentioning
confidence: 99%
“…Likewise, storing cash at home is difficult "because such sums are easily eroded by many kinds of risk and pressure: they can be stolen or lost, or used up in trivial expenditure, or claimed by family and neighbours falling on hard times" (Rutherford, 2000, p. 11-12). Bachas et al (2016) provide evidence from Mexico that saving informally is difficult and using bank accounts to save helps solve self-control problems. As reported by Rutherford (2003) and Nasrin et al (2016), most slum dwellers in Dhaka do not hold bank accounts; and those who do rarely use them because "bank norms are so stiff that it is not convenient to use [them] regularly" (Rutherford, 2003, p. 51 (Ashraf et al, 2006;de Mel et al, 2013).…”
Section: Datasetmentioning
confidence: 99%
“…3 Other cash savings: savings with shopkeeper or employer, farmer groups and village leader. 4 In Uganda, data for having "ever" received a loan; in Malawi: data on having received a loan in the last 6 months, and we control at baseline with a varible on having "ever" received a loan. …”
Section: Deposits and Feesmentioning
confidence: 99%
“…In contrast to the excess consumption associated with credit cards, debit cards were studied by Reference [32], and it was found that consumers who received a debit card as a result of financial transfer operations, tended to voluntarily reduce their consumer spending, and thus, managed to save money. Thus, a part of the population that is included in the category of the population affected by poverty has a chance to change their consumption style in order to improve their own financial situation.…”
Section: Expected Benefits From Bank Cardsmentioning
confidence: 99%